Compact City : Menuju Sustainabilitas Terhadap Fenomena Urban Sprawl - Gde Bagus Andhika Wicaksana; Ida Bagus Gede Parama Putra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2019)
The rise of urban sprawl - menggurita is a phenomenon resulting from the growth and development of the city as a center of activity and the economy. The sprawl is characterized by the growth of low-density settlements that scattered randomly in suburban areas or peripherals. The growth spread like the octopus tentacles that propagate this causes various effects of negative externalities in the form of pollution, energy efficiency, economic equity, and transportation problems. Based on these problems, this study aims to provide a solution interpretation in dealing with the phenomenon of a city that is overflowing, by studying deeper into the compact city as compacting system or combining the functions of land use and urban activities that are expected to reduce the effects of urban sprawl. By using the critical review method, which focuses on providing explanations, interpretations of the analysis from several literature selected to be used as a reference in finding solutions according to urban compaction loci in dealing with urban sprawl problems. From critical review searches, it is concluded that a compact city is an innovative solution to the phenomenon of random city development (urban sprawl development). One of them by implementing Urban Growth Boundaries (UGB) provides an alternative solution to the problem of sprawl. The compact city promises efficiency in city management. By maximizing the livability of the city and city services, the compactness form symbolizes a form that integrates all the optimal conditions of the city for the sustainability of a city in the future.